INTEGRASI PEMBELAJARAN MATEMATIKA DENGAN PLATFORM DIGITAL DALAM KURIKULUM MERDEKA DI SEKOLAH DASAR - Indah Rukmiyati Sovia Pambo; Syamsiar Syamsiar; Herliana Sabu; Sulis Tiawati; Imrona Hayati (Al-Rabwah, 2026)
The fast advancement of information and communication technology (ICT) has led to major changes in the field of education, including the teaching and learning of mathematics in elementary schools. The integration of technology within the Merdeka Curriculum plays an essential role in creating effective, innovative, and student-centered learning. Digital technologies such as instructional videos, educational applications, and interactive software can help visualize abstract mathematical concepts, making them easier for students to understand in accordance with their cognitive development stages. This study employs a literature review method by analyzing relevant scientific articles obtained through Google Scholar. The results show that integrating digital platforms can boost student engagement and motivation, improve understanding of mathematical concepts, and foster century skills such as critical thinking, creativity, collaboration, and problem-solving. However, its application still encounters several obstacles, including limited infrastructure, insufficient digital literacy among teachers, and uneven access to technology across schools. Therefore, improving teacher competencies, ensuring equitable technological facilities, and providing continuous policy support are necessary to optimize the use of digital platforms in mathematics learning.